Profiling nutraceuticals in bael [Aegle marmelos (L.) Correa] at various stages of fruit development. Issue 2 (3rd March 2016) - Bhattacherjee, A. K.; Dikshit, A.; Kumar, P. Chethan; Pandey, D.; Tandon, D. K.
ABSTRACT: Bael [ Aegle marmelos (L.) Correa], a medicinally important fruit tree grown on the Indian sub-continent, contains two bio-active furanocoumarins, marmelosin and psoralen, with pharmacological properties, plus two powerful groups of natural anti-oxidants, polyphenols and tannins. The present investigation aimed to measure the levels of these nutraceuticals at various stages of fruit development [150–345 days after fruit set (DAFS)] in two promising selections of bael from the Institute, CISH B-1 and CISH B-2, using a simple high performance liquid chromatography (HPLC) technique. Marmelosin and psoralen were extracted from 5 g of homogenised fruit mesocarp using benzene, while tannins were extracted as tannic acid with 80% (v/v) methanol in water. Polyphenol concentrations were measured spectrophotometrically at 760 nm using Folin-Ciocalteu reagent. The concentrations of marmelosin declined from 1, 660 and 726 µg g − 1 at 150 DAFS, to 523 and 170 µg g − 1 at 345 DAFS in CISH B-1 and CISH B-2, respectively, whereas psoralen concentrations decreased from 216 and 41 µg g − 1 to 102 and 9 µg g − 1 during the same growth period in CISH B-1 and CISH B-2, respectively. Tannic acid concentrations decreased from 1.65 and 2.02 g 100 g − 1 at 150 DAFS, to 1.52 and 1.54 g 100 g − 1 at 345 DAFS in CISH B-1 and CISH B-2, respectively. The concentrations of total polyphenols did not show any significant changes in either bael selection over the same growth period. The concentrations of marmelosin and psoralen in CISH B-1 were highest in October (150 DAFS), while these values peaked in November (190 DAFS) in CISH B-2. The results suggest that fruit harvested at an early stage of growth (October–November) contained higher concentrations of nutraceuticals, increasing their suitability for fruit processing and use in the phyto-pharmaceutical industries.